Calcium and Neurogenesis in Alzheimer's Disease - Wang, Junming; Sun, Chenyou (Frontiers in Neuroscience, 2010)
It was evidenced that impairment of calcium homeostasis is a potential mechanism in the development of Alzheimer’s disease (AD). It remains, however, unclear how the calcium signaling are associated with in Alzheimer’s disease progression. Here we review recent studies to discuss the relationship among the signaling of intracellular calcium concentration, neurogenic activity, and AD progression. Analyzing these findings may provide new ideas to improve the neurogenic status in pathological processes in the aging brain.